Electrical Machines: Mathematical Fundamentals of Machine Topologies - Gerling, Dieter (Springer, 2015)
Electrical Machines and Drives play a vital role in industry with an ever increasing importance. This fact necessitates the understanding of machine and drive principles by engineers of many different disciplines. Therefore, this book is intended to give a comprehensive deduction of these principles. Special attention is given to the precise mathematical deduction of the necessary formulae to calculate machines and drives, and to the discussion of simplifications (if applied) with the associated limits. So the book shows how the different machine topologies can be deduced from general fundamentals, and how they are linked.